Confiabilidade do exame de audiometria tonal baseado no cálculo de incerteza de medição ISO 8253-1:2010 - Silva, Denise Torreão Corrêa da (2016)
To estimate the measurement uncertainty of the pure-tone audiometry by air-conduction, in the frequencies from 250 Hz to 8000 Hz, and bone-conduction, at frequencies of 500 Hz to 4000 Hz. Method: This is an observational, descriptive and cross sectional study. Accuracy measurement tests under repeatability conditions were conducted (same measurement procedure, operator, measuring system, operating conditions and site, in a short time interval). Each of the nine participants took part in two trials with five repetitions each through air and bone conduction, in the right and left ear. In Trial 1 the interval between each repetition was five minutes. In Trial 2 the interval between repetitions was sixty minutes. To calculate the combined uncertainty the type A uncertainty, derived from repeatability, and Type B uncertainty derived from the audiometer calibration certificate, the audiometer resolution, and the conditions of the test environment were considered. Results: There was no statistically significant difference intra-individuals in different time intervals (p> 0,05), in both air and bone conduction. The median of type A uncertainty ranged from 0 dB to 2,7 dB in the right ear, and 0 dB to 3,5 dB in the left ear for air conduction. In bone conduction the median of type A uncertainty ranged from 2.2 dB to 2.7 dB in both ears. Type B uncertainties, for air and bone conduction, derived from the contribution of the equipment used for the test (0,4 dB), of the equipment resolution (1,4 dB), and the test environment (5,0 dB). Considering the median of type A uncertainty derived from accuracy measurement, and type B uncertainties mentioned above, the estimated of measurement uncertainty of pure tone audiometry, air and bone conduction, in this study, for the confidence level of 95% (k=1.96) and 95.45% (k=2.0) were 10 dB or 11 dB, for the frequencies tested, in both Trials 1 and Trial 2, in both ears. Conclusions: This study demonstrates the feasibility of accuracy measurement tests under repeatability conditions, as proposed in this work. In this study the contribution of type B uncertainties, derived from the audiometer calibration certificate, potentiometer and test environment, this latter being more prevalent, was higher than that of type A uncertainty derived from repeatability, indicating the need to keep control of these variables. The expression of measurement uncertainty can increase even more the sensitivity and specificity of audiometry, respectively increasing the rate of true positives and true negatives, since it is considered the gold standard. In this study the expanded uncertainty, for the confidence level of 95% and 95,45% ranged between 10 and 11 dB, in air and bone conduction. The reliability of the pure-tone audiometry test depends on the expression of its uncertainty; only so results obtained with the same subject in different places and times can be compared. Therefore the expression of uncertainty should be taken into consideration when delivering results and in preparing reports, for subsidizing decisions on hearing aids prescription, selection and adaptation procedures, as well as assessment of social security benefit payments, labor actions and health surveillance actions